Karduniaš. Babylonia under the Kassites / Karduniaš. Babylonien in der Kassitenzeit - Babylonia under the Kassites / Volume 2 Archaeological studies (Karduniaš. Babylonia under the Kassites / Karduniaš. Babylonien in der Kassitenzeit - Babylonia under the Kassites, 2017)
Karduniaš, as the kingdom of the Kassites in Babylonia was called in ancient times, was the neighbor and rival of great powers such as Egypt, the Hittites, and Assyria. But while our knowledge of the latter kingdoms has made huge progress in the last decades, the Kassites have until recently been largely ignored by modern scholarship. Recently a number of scholars have embarked on research into different aspects of Late Bronze Age Babylonia. The desire to share the results of these new investigations resulted in an international conference, which was held at Munich University in July 2011. The presentations given at this meeting have been revised for publication in the current volume.This book gives an overview of current research on the Kassites and is the first larger survey of their culture ever. An invaluable introduction by Kassite expert Professor John A. Brinkman is followed by seventeen specialist contributions investigating different aspects of the Kassites. These include detailed historical, social, cultural, archaeological, and art historical studies concerning the Kassites from their first arrival in Mesopotamia, during the period when a Kassite Dynasty ruled Babylonia (c. 1500-1550 BC), and in the subsequent aftermath. Concentrating on southern Mesopotamia the contributions also discuss Kassite relations and presence in neighboring regions.The book is completed by a substantial bibliography and a detailed index.